Faster male displays and less complex choice are more attractive to female fiddler crabs as they reduce search costs - Sanches, Fábio Henrique Carretero [UNESP]; Costa, Tânia Marcia [UNESP]; Barreto, Rodrigo Egydio [UNESP]; Backwell, Patricia R.Y. (Elsevier, 2017)
Females that quickly and accurately locate and assess males can reduce their risks of predation, dehydration and heat stress while mate searching. Here we measured the accuracy and time it took female fiddler crabs, Uca mjoebergi, to approach robotic claws that simulated males' courtship signals. We ran six experiments: three one-choice experiments varying in waving display rate (fast, medium and slow) and three three-choice experiments with increased number of displays (all with fast wave rate) and complexity (each one at the three different rates; and the three different rates presented at different distances, with the fast wave rate further from the female and the slow wave rate closer to the female). Females approached all waving robots with an accuracy of 9–18°. They approached faster-waving claws more quickly even when they were presented in sets of three claws, but it took females longer to approach a claw in the more complex situation, with claws waving at different rates and distances. Females may approach waving claws more rapidly simply because they present a more continuous and less ambiguous stimulus. The results suggest that high signalling rates may attract females because they reduce female search costs, and they may or may not additionally signal male quality.
Keywords: accuracy; mate choice; robotic crab; sexual selection; waving display